Protecting people and wildlife from the potential harms of drone use in biodiversity conservation: interdisciplinary dialogues - Jackman, A.; Millner, N.; Cunliffe, A.M.; Laumonier, Y.; Lunstrum, E.; Paneque-Gálvez, J.; Wich, S.A. (Bristol University Press, 2023)
In this policy intervention, we recount the process of producing a policy briefing targeting researchers and practitioners who use drones in biodiversity conservation. We use the writing process as a springboard to think through the ways that interdisciplinary exchange has and might further inform the ethical use of new technologies, such as drones. This approach is vital, we argue, because while drones may be deployed as tools that enable or empower forest, wildlife or habitat monitoring practices, so too can they be variously disruptive, repurposed and/or exceed these applications in significant ways. From questions of surveillance and capture, data ownership and security, to noise disruption, drone use requires careful and critical reflection, particularly in sensitive contexts. Yet, interdisciplinary exchange attentive to the ethical, social and experiential dimensions of drone use remains patchy and thin. To this end, this intervention reflects on the process of a group of scholars from ecological, environmental and social science backgrounds coming together in an interdisciplinary project grappling with diverse issues around responsible conservation drone use. After recounting our methodology, including the surprises and learning that emerged in practice, we contextualise the key themes we chose to foreground in our published policy briefing. We conclude by connecting our collaboration with wider actions and energies in the context of existing (conservation) drone policy and practice, while underscoring our contributions to existing work.